2016
DOI: 10.4103/1947-489x.210210
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' and doctor's attitude to patient education barriers in Najran armed forces Hospital, Saudi Arabia

Abstract: Objective: We aimed to assess nurses' and doctor's attitude to patient education barriers in Najran Armed Forces Hospital (NAFH). Materials and methods: This is a cross-sectional study targeting health care professionals in NAFH. The study was conducted during April 2015. The studied participants were all nurses and doctors who work in NAFH. Anonymous self-administered questionnaires were used to obtain information on sociodemographic background including age, gender, marital statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…Other factors may be over lode on nurses due to of the shortage of staff and it may be also due to the restrictions of the hospital policy which allocate contraception education to the gynaecology doctors. This reasons are supported by a study conducted by Harrabi, Al Ghamdi and Xilavi [30]. They reported that nurses believed shortness of time (68.8%), lack of common language and culture to communicate with the patient (91.6%) and lack of patients' motivation to learn (85.7%) were the most important causes of the insufficiency of patient education about contraceptives [30].…”
Section: Discussionsupporting
confidence: 58%
“…Other factors may be over lode on nurses due to of the shortage of staff and it may be also due to the restrictions of the hospital policy which allocate contraception education to the gynaecology doctors. This reasons are supported by a study conducted by Harrabi, Al Ghamdi and Xilavi [30]. They reported that nurses believed shortness of time (68.8%), lack of common language and culture to communicate with the patient (91.6%) and lack of patients' motivation to learn (85.7%) were the most important causes of the insufficiency of patient education about contraceptives [30].…”
Section: Discussionsupporting
confidence: 58%
“…The present qualitative study findings were found consistent with studies of (24)(25)(26)(27)(28)(29)(30)(31)(32) who had been studied weaknesses and threats in variables of barriers and challenges of health education at different healthcare and…”
Section: Zagazig Nursing Journalsupporting
confidence: 91%